(untitled) (International Journal of Physiotherapy, 2016)
Background: Individuals with the age of 60 years and above may present with the symptoms of imbalance and body instability. Therefore, balance related activities such as standing, getting up from chair; walking becomes difficult which leads to fall. Also, old people are more prone to frequent diseases, sickness and also have limited regenerative capabilities when compared to other adults. So, the purpose of this study was to find out the comparison of multisensory versus strengthening exercises on functional mobility and balance in elders. Methods: 45 subjects with good comprehension were selected for the study based on inclusion and exclusion criteria and were randomized into three groups Group A(15), Group B(15), Group C (15) by simple random sampling technique. The subjects in Group A received Multisensory exercises whereas Group B received strengthening exercises and Group C underwent Walking. The subjects were made to do these exercises for five days a week for a total duration of 6 weeks. The baseline values and post –test values were assessed with Timed ‘up and go’ test (TUG) and Guralnik test battery. Results: The mean difference between subjects trained with Multisensory exercises (Group- A) and Walking (Group-C) is greater than Multisensory exercise (Group-A) and Strengthening exercise (Group B), Walking (Group C)and Strengthening(Group B)for both Timed up and go test (P<0.0001) and Guralnik test battery(P=0.05) (Graph 1, 2). This shows that multisensory exercises are effective compared to strengthening exercises and walking. Conclusion: In this study, multisensory exercises showed more improvement in mobility and balance. So, multisensory exercise can be considered as an adjunct with other exercises in rehabilitation of the elderly subjects with balance impairment.